PERLINDUNGAN HUKUM TERHADAP KONSUMEN KLAUSULA EKSONERASI PADA JUAL BELI ON LINE - Dhanti, Wa Ode Hasmi; Andara, Darojatun; Rahman, Muhammad Ikhwan (Muhammadiyah Makassar University, 2024)
ABSTRACT The purpose of this study is to determine the form of application of exoneration clauses in online buying and selling according to Law Number 8 of 1999 concerning Consumer Protection and to determine the form of consumer protection for the application of exoneration clauses in online buying and selling. The research method used with a normative approach or legal research literature legal research conducted by examining existing library materials. Legal research by describing completely and systematically about several aspects under study, especially regarding the regulation of the application of exoneration clauses in relation to consumer protection. The results of the research The form of application of exoneration clauses in online buying and selling according to Law Number 8 of 1999 concerning Consumer Protection, including Disclaimer of responsibility can be included by the seller or e-commerce platform, Limitation of Financial Responsibility, E-commerce platforms or sellers can choose to exclude their responsibility for certain categories of damage or conditions that are considered to be beyond the scope of their control, Non-Warranty Clauses, also known as As-Is Clauses, allow the seller to state that the product is sold in its current condition, without any warranty or guarantee regarding its quality, suitability, or fitness for a particular purpose, Limitation of Time for Filing Claims, and Jurisdictional or Territorial Limitations E-commerce platforms or sellers may include provisions describing the particular legal jurisdiction in which the dispute will be resolved, along with limitations on the jurisdiction in which the clause applies.Forms of legal protection for consumers for the application of exoneration clauses in online buying and selling include thorough legal examination, consumer education, advocacy, use of legal alternatives, and law enforcement: It is essential to ensure that exempting provisions that violate consumer protection laws are successfully prosecuted to prevent violations of applicable laws. To monitor and report violations, cooperation between government, law enforcement, and non-profit organizations is required. Keywords: Consumer Protection, Exoneration Clause, Online Buying and Selling